Optimised operational management of distribution grids by utilising flexibilities through automation of electrical assets using a multi-agent-system approach - Riebesel, David; Schramm, Simon; Mehlmann, Gert; Luther, Matthias (27th International Conference on Electricity Distribution (CIRED 2023), 2023)
By reducing inertia and increasing the number of distributed generation and load units, the energy transition places additional stress on the distribution grid. However, there is an opportunity to take advantage of the new grid structure. This can be achieved with a certain degree of automation through information and communication technology (ICT). A multi-agent system (MAS) control approach was used to address this problem and take advantage of the decentralized topology. Through the MAS, each generation/load unit gains a degree of autonomy and intelligence while being able to communicate with others, in this case the immediate neighborhood. Under the assumption of existing load forecasting, a local control algorithm for DERs is derived. This improves the operational management of distribution networks by reducing the residual load through a decentralized approach. The proof of concept is validated in a co-simulation using a shared memory (SHM) interface to connect the electrical network model with the MAS logical model.<br
Keywords: condition monitoring; distributed power generation; distribution networks; load forecasting; multi-agent systems; power engineering computing; power grids; communication technology; decentralized approach; decentralized topology; distributed generation; distribution grid; distribution networks; electrical assets; electrical network model; energy transition places additional stress; grid structure; load forecasting; load units; local control algorithm; MAS logical model; multiagent system control approach; multiagent-system approach; optimised operational management; residual load